2010
DOI: 10.1021/la1003808
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Lyophilization of Lipid Nanocapsules with Fluorescence Correlation Spectroscopy

Abstract: This paper describes characterization of lyophilized lipid nanocapsules loaded with Alexa 488 by fluorescence correlation spectroscopy (FCS). Fluorimetry analysis of nanocapsules containing selfquenching concentrations of 5-(and-6)-carboxyfluorescein was performed to establish a point of reference for FCS. FCS results complemented the results obtained by fluorimetry for a bulk nanocapsule solution and provided additional information about the size and dye retention by individual nanocapsules. Using this method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…7,9 However, we recently overcame the stor-age issue for lipid nanocapsules by using an optimized lyophilization procedure that allows us to store lipid nanocapsules over long periods of time at Ϫ20 °C as a lyophilized powder. 19 As a result, we returned to developing light-addressable lipid nanocapsules as a general caging platform for bioactive molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,9 However, we recently overcame the stor-age issue for lipid nanocapsules by using an optimized lyophilization procedure that allows us to store lipid nanocapsules over long periods of time at Ϫ20 °C as a lyophilized powder. 19 As a result, we returned to developing light-addressable lipid nanocapsules as a general caging platform for bioactive molecules.…”
mentioning
confidence: 99%
“…Unfortunately, the lipid vesicles were fragile and could not be stored in solution for more than a few days. This practical constraint prompted us to explore a range of more robust nonlipid-based nanocapsules, including ones formed by colloidal templating in silica and polymer-based nanocapsules. , However, we recently overcame the storage issue for lipid nanocapsules by using an optimized lyophilization procedure that allows us to store lipid nanocapsules over long periods of time at −20 °C as a lyophilized powder . As a result, we returned to developing light-addressable lipid nanocapsules as a general caging platform for bioactive molecules.…”
mentioning
confidence: 99%
“…Our group has been interested in developing techniques that are capable of probing the structure of biological signaling networks with high spatial and temporal resolution. Towards this end, we have developed a method that employs nanocapsules as physical cages to entrap bioactive molecules within the capsules until the capsules are burst open using a single nanosecond laser pulse 18 . Our strategy for using nanocapsules in an in vitro cell culture setting is shown in figure 1.…”
Section: Introduction: Single-site Delivery Of Biological Stimuli mentioning
confidence: 99%
“…We have demonstrated that this method can release the contents of a nanocapsule onto cells with sub-micron spatial resolution and sub-microsecond temporal resolution 18 . We have also delivered a wide range of bioactive stimuli to cells, including small molecules and large protein biomolecules.…”
Section: Introduction: Single-site Delivery Of Biological Stimuli mentioning
confidence: 99%